2005
DOI: 10.1111/j.1430-9134.2005.00032.x
|View full text |Cite
|
Sign up to set email alerts
|

Product‐Line Length as a Competitive Tool

Abstract: The increasing number of consumer goods and services offered in recent years suggests that product‐line extensions have become a favored strategy of product managers. A larger assortment, it is often argued, keeps customers loyal and allows firms to charge higher prices. There is disagreement, however, about the extent to which a longer product line translates into higher profits. We develop an econometric model derived from a game‐theoretic perspective that explicitly considers firms' use of product‐line leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(123 citation statements)
references
References 43 publications
5
116
0
2
Order By: Relevance
“…From an empirical perspective, Walters and Mackenzie (1988) report that loss-leader pricing produced only a small increase in store traffic. Recent empirical research in marketing (e.g., Bayus andPutsis 1999, Draganska andJain 2005) examines the relation of prices with product variety and other marketing mix variables that are endogenously determined by firms and their impact on market shares. Chen et al (1999) also study the impact of basket shopping consumers.…”
Section: Related Literaturementioning
confidence: 99%
“…From an empirical perspective, Walters and Mackenzie (1988) report that loss-leader pricing produced only a small increase in store traffic. Recent empirical research in marketing (e.g., Bayus andPutsis 1999, Draganska andJain 2005) examines the relation of prices with product variety and other marketing mix variables that are endogenously determined by firms and their impact on market shares. Chen et al (1999) also study the impact of basket shopping consumers.…”
Section: Related Literaturementioning
confidence: 99%
“…However, relatively little is known empirically about how product assortment composition varies across stores within a supermarket chain or across supermarket chains. Most existing empirical studies have focused on assortment size rather than assortment composition (Bayus and Putsis 1999, Putsis and Bayus 2001, Kadiyali et al 1999, Draganska and Jain 2005, Watson 2009, Richards andHamilton 2006, Misra 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Research on product lines and product variety can be found amongst both business and economics scholars (e.g., Berry and Waldfogel (2001), Broniarczyk, Hoyer, and McAlister (1998), Gourville and Soman (2005), Draganska and Jain (2005), Richards and Hamilton (2006), Misra (2008), Quan and Williams (2014), and Conlon and Mortimer (2015)). Many of these contributions are focused on modeling supply-side decisions, including the decisions of manufacturers to extend or shorten available product lines, and the decisions of retailers to stock particular product varieties.…”
Section: Boundariesmentioning
confidence: 99%